Pengaruh Dissatisfaction, Variety Seeking, Electronic Word of Mouth, dan Religiosity terhadap Brand Switching Produk Kosmetik Lain ke Kosmetik Wardah pada Mahasiswi Universitas Negeri Padang - Ardina Safitri; Whyosi Septrizola (Jurnal Kajian Manajemen dan Wirausaha, 2019)
Purpose- This study aims to determine the effect of dissatisfaction, variety seeking, electronic word of mouth, and religiosity on the brand switching of other cosmetic products into Wardah cosmetics.Methodology - The population in this study were students from Padang State University who used Wardah cosmetics. The sampling technique is nonprobability sampling, with a purposive sampling method. The number of samples obtained was 394 respondents from the population. The data analysis technique used is multiple linear regression analysis using SPSS software.Finding - The results of the study show that simultaneously each variable used significantly influences brand switching from other cosmetics to Wardah cosmetics. Partially, the dissatisfaction, variety safety, electronic word of mouth, and religiosity variables have a positive and significant effect on brand switching from other cosmetics to Wardah cosmetics. The coefficient of determination for dissatisfaction (X1), variety seeking (X2), electronic word of mouth (X3), and religiosity (X4) variables accounted for 43.2% for brand switching from other cosmetics to Wardah cosmetics while 56.8% was influenced by other factors. Keywords: Dissatisfaction, Variety Seeking, Electronic Word of Mouth, Religiosity, and Brand Switching